2003
DOI: 10.1530/eje.0.1480519
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of CYP19 gene expression in primary human osteoblasts: effects of vitamin D and other treatments

Abstract: Objective: Extragonadal estrogen biosynthesis is relevant for the regulation of bone metabolism. The aims of this paper were: (i) to examine CYP19 (aromatase) gene expression in primary cultures of osteoblasts under several hormone and cytokine treatments and (ii) to study the promoter usage of CYP19 in these cells. Methods: Primary cultures of osteoblasts were obtained from healthy donors. The effects of vitamin D and other factors on CYP19 expression were analysed by semiquantitative RT-PCR. Furthermore, CYP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
40
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 45 publications
9
40
0
Order By: Relevance
“…Consistently with results obtained in our previous study using primary hOBs (22), luciferase assays showed that pII, I.3 and I.4 promoters were active in MG-63 cells. Here we report that the sequence containing promoter pII up to exon I.3 (2 221 to þ 1) displayed high activity in MG-63 cells.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Consistently with results obtained in our previous study using primary hOBs (22), luciferase assays showed that pII, I.3 and I.4 promoters were active in MG-63 cells. Here we report that the sequence containing promoter pII up to exon I.3 (2 221 to þ 1) displayed high activity in MG-63 cells.…”
Section: Discussionsupporting
confidence: 91%
“…Our results therefore underscore the importance of exon I.6 in the regulation of pII or I.3 promoter activity in osteoblasts. Regarding promoter I.4, an important activity was observed in MG-63 cells, consistent with our previous findings in hOBs and those of other groups (15,16,22). Additionally the presence of an enhancer element in exon I.4 (þ 71 to þ 328) was demonstrated.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Exon I.4 is the preferential transcript in adipose tissue, which also transcribes PII, I.3 and I.6 in smaller amounts (3,10,18). The main promoter used in bone tissue seems to be I.4, but bone cells have also been shown to express exons PII, I.6, I.3, I.2 and I.f in some culture conditions (16,19,20). In fact, a phenomenon of promoter switching depending upon the regulatory factors present in the media, including hormones and cytokines, and cell differentiation inducers has been shown in many tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Expression of exon I.2 was first reported in the placenta, but it is also expressed in other tissues, including bone. Indeed, Enjuanes et al (20) have recently reported that 1,25-dihydroxyvitamin D3 and glucocorticoids induce I.2 expression by The mechanism underlying the association between CYP19 alleles and bone mass is unclear. It could be directly related to differences in the transcription response to promoters.…”
Section: Discussionmentioning
confidence: 99%